Penguatan Nilai Moderasi Beragama melalui Ajaran Pendidikan Agama Islam - solihin, Mohamad; Hakim, Lukman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Religious moderation is an important foundation for creating harmony in rural communities that often have diverse dynamics. Islamic education in the village has a strategic role in instilling the values ​​of religious moderation, especially in the younger generation and the general public. This study aims to analyze the role of Islamic education teachings in Semampir village in strengthening the values ​​of religious moderation. A phenomenological approach with qualitative research is used with in-depth interview methods, field observations and literature literacy studies. The results of the study indicate that Islamic education teachings can strengthen the values ​​of religious moderation, including: 1) Instilling Tolerance Values ​​2) strengthening noble morals 3) involvement of religious leaders. Meanwhile, the implementation of religious moderation values ​​in this village is carried out through various approaches that involve the active participation of the Semampir village community. Some concrete steps taken include religious studies, interfaith dialogue, and socio-religious activities.